KATALOGISASI KOLEKSI PERPUSTAKAAN KECIL DAERAH SINDANGLAYA - Najlaa Syarif; Evi Nursanti Rukmana; Asep Saeful Rohman (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
Library services are an illustration of the fulfillment of library functions. One of the services that must be provided in the library is a catalog service. A service that makes it easier for users to find the collection they need in addition to asking a reference service. The catalog has three objects as mentioned by Cutter, namely the find function, the collect function, and the select function. In addition, the existence of a catalog can facilitate librarians in the collection development process. Therefore, a catalog should be in every library. The purpose of writing is to find out whether the use of catalogs in the intended library has been effective? Has the library implemented a catalog service? Is the SLiMS application in the Library effective to use? The author uses qualitative research methods so that the results obtained can be in accordance with the facts that appear and are seen when researchers observe the state of the object, namely the Sindanglaya Small Library. With the results of the study that the Sindanglaya Regional Small Library has not applied catalog services properly, only relying on the arrangement on the bookshelves so that researchers work with managers to use online catalogs by inputting data collections from the library using the SLiMS application. , ,